ROS in the Male–Female Interactions During Pollination: Function and Regulation - Zhang, Ming Jun; Zhang, Xian Sheng; Gao, Xin-Qi (Frontiers in Plant Science, 2020)
The male–female interactions in pollination mediate pollen hydration and germination, pollen tube growth and fertilization. Reactive oxygen species (ROS) derived from both male and female tissues play regulatory roles for the communication between the pollen/pollen tube and female tissues at various stages, such as pollen hydration and germination on the stigma, pollen tube growth in the pistil and pollen tube reception in the female gametophyte. In this minireview, we primarily summarize the recent progress on the roles of ROS signaling in male–female interactions during pollination and discuss several ROS-regulated downstream signaling pathways for these interactions. Furthermore, several ROS-involved downstream pathways are outlined, such as Ca2+ signaling, cell wall cytomechanics, the redox modification of CRP, and cell PCD. At the end, we address the roles of ROS in pollen tube guidance and fertilization as future questions that merit study.